Serum gamma-glutamyl transferase level in acute stroke - Singh, Lagendra Kumar; Pradhan, Sourabh; Dash, Laxmikanta; Pradhan, Jagannath; Raul, Umakanta; Meher, Rajesh Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Stroke is the second leading cause of death worldwide, causing 6.2 million deaths in 2011. Serum Gamma-Glutamyl Transferase (GGT) has been conventionally considered as a marker of excessive alcohol intake and/or liver dysfunction. There are accumulating evidences suggesting association of raised serum GGT level in stroke. So, this study was conducted to determine the association between the serum GGT level and stroke in population without history of alcohol consumption. Methods: This cross-sectional comparative study was carried out at Department of General medicine, Veer Surendra Sai Institute of Medical Sciences and Research (VIMSAR), Burla from November 2016 to October 2018. 100 cases and 100 controls were included in this study. Cases were the patients admitted to Department of General Medicine, VIMSAR, Burla, presenting within 24 hours of first episode of stroke. Controls were the age (+/-5 years) and sex matched healthy attendants of the patients. Alcoholics or patients suffering from hepatitis, cirrhosis of liver, cholestasis or patients taking drugs like Phenytoin, Valproic acid, Carbamazepine etc or patients with past episode of stroke were excluded from this study. Serum GGT level of both cases and controls were measured and compared. Results: In stroke patients, the mean serum GGT level was 54.95 IU/L with standard deviation of 20.54. In controls, the mean serum GGT level was 32.14 IU/L with standard deviation of 5.07. The p-value was less than 0.0001 i.e. highly significant. Conclusions: Serum GGT level is significantly increased in stroke patients than healthy persons without stroke.